Quality of Life in Papillary Thyroid Microcarcinoma Patients Undergoing Radiofrequency Ablation or Surgery: A Comparative Study - Lan, Yu; Luo, Yukun; Zhang, Mingbo; Jin, Zhuang; Xiao, Jing; Yan, Lin; Zhu, Yaqiong (Frontiers in Endocrinology, 2020)
Objective: Papillary thyroid microcarcinoma (PTMC) has a good prognosis and a long survival time. Health-related quality of life (HRQoL) is vital for PTMC patients during their survivorship. Ultrasound (US)-guided radiofrequency ablation (RFA), which has high efficacy and safety, is recommended as an alternative treatment to surgery for the patients with low-risk PTMC. However, the assessment of QoL of patients with PTMC has not been specially reported. The purpose of our study was to compare the HRQoL of patients with PTMC who underwent RFA and those who underwent surgery. Methods: From October 2019 to December 2019, 88 PTMC patients were enrolled in our study, including 54 in RFA group and 34 in surgery group. We used three questionnaires which included the 36-item short form health survey (SF-36), thyroid cancer-specific quality of life (THYCA-QOL), and Fear of Progression Questionnaire-Short Form (FoP-Q-SF) for each patient to evaluate their scores of HRQoL. The scores were compared after adjusting for age, sex, medical expense, and follow-up time. Results: According to the SF-36, the scores of the domain for the role limitation due to physical problems and emotional problems (RP, RE) as well as Physical Component Summary (PCS) showed a significant negative linear association between the RFA group and surgery group: RP coefficient [coef]−22.613 [confidence interval (CI) −33.504 to −11.723], p < 0.001, RE (coef: −21.901 [CI −36.737 to −7.064], p = 0.004), and PCS (coef: −8.312 [CI −13.694 to −2.930], p = 0.003). The THYCA-QOL showed that the scores of the surgery group were higher than that of the RFA group regarding scars (coef: 10.246 [CI 1.330 to 19.162], p = 0.025 according to the multivariate analysis), suggesting a higher level of complaint in the surgery group. There was no statistically significant difference in the scores of FoP-Q-SF between the two groups. Conclusions: In patients with PTMC, US-guided RFA offers advantage over surgery in terms of HRQoL, which supports the role of RFA as an alternative strategy to surgery.